2009
DOI: 10.1007/s10551-009-0183-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Giving Lead to Getting? Evidence from Chinese Private Enterprises

Abstract: donation, philanthropy, private enterprise, political connections, property rights,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(128 citation statements)
references
References 37 publications
4
123
0
1
Order By: Relevance
“…Scholars also find that Chinese companies can build political connection through charity activities, and then get more loans, investing opportunities, etc. (Su & He 2009).…”
Section: External Political Pressurementioning
confidence: 99%
“…Scholars also find that Chinese companies can build political connection through charity activities, and then get more loans, investing opportunities, etc. (Su & He 2009).…”
Section: External Political Pressurementioning
confidence: 99%
“…Although previous studies have examined the potential instrumental benefits of corporate community initiatives (Fooks et al, 2013;Saiia et al, 2003), very few studies (but see Zhao, 2012) investigate how companies exploit these initiatives to seek legitimacy from the state and other key institutional actors. Some studies, such as the one conducted by Su and He (2010), have shown that firms engage in philanthropy to maximise the firm's benefits, not in the form of an immediate economic return, but rather in order to maximise their 'political return', which is designed to circumvent regulation or seek to be better protected from government intervention or legislation. Under such circumstances, any mismanagement of CSR as part of a firm-level strategy could thus weaken the firms' competitive position relative to their rivals in the country, and undermine their legitimacy, which in turn could result in a long-term disadvantage for the firm (Baron, 2001).…”
Section: Corporate Social Responsibility: Discretionary Strategic Ormentioning
confidence: 99%
“…have been distinctly lacking. While some scholarship (Su and He, 2010;Zhao, 2012) concerned with CSR has answered 'Yes' to this question, other questions about 'How', 'Why' and 'To what extent' multinationals gain legitimacy via their CSR policies and practices remain poorly addressed. In this paper we respond to this gap in the literature and, in the process, contend that when MNEs operate in countries where the state exerts considerable power and control over businesses, such as in Sri Lanka, CSR can prove to be an important legitimisation tool by which MNEs can gain recognition (and support) from the state and other institutional actors (Feng and Wang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Extant research typically explains corporate philanthropy as a function of societal expectations (Adams and Hardwick 1998;Brammer and Millington 2004;Crampton and Patten 2008;Galaskiewicz and Burt 1991;Marquis et al 2007) or in terms of reputation and financial management strategies (Brammer and Millington 2005;Lev et al 2010;Saiia et al 2003;Su and He 2010). Most research emphasizes structural institutional factors that explain variance in firms' overall levels of annual giving.…”
Section: Introductionmentioning
confidence: 99%